2021
DOI: 10.3389/fnagi.2021.679282
|View full text |Cite
|
Sign up to set email alerts
|

Older Compared With Younger Adults Performed 467 Fewer Sit-to-Stand Trials, Accompanied by Small Changes in Muscle Activation and Voluntary Force

Abstract: Background: Repetitive sit-to-stand (rSTS) is a fatigue perturbation model to examine the age-effects on adaptability in posture and gait, yet the age-effects on muscle activation during rSTS per se are unclear. We examined the effects of age and exhaustive rSTS on muscle activation magnitude, onset, and duration during ascent and descent phases of the STS task.Methods: Healthy older (n = 12) and younger (n = 11) adults performed rSTS, at a controlled frequency dictated by a metronome (2 s for cycle), to failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Age-related decline of muscle function has been attributed to changes in both the nervous and muscular systems 2 . Prior work has indicated that there is progressive decline in muscle function (e.g., strength) beginning around 30 years of age with an accelerated loss after 60 years of age 3 , 4 . The age-related reduction in muscle strength is notably greater than the loss of muscle mass 5 , which indicates that other changes in the neuromuscular system beyond atrophy are mechanistically associated with the loss of muscle function 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Age-related decline of muscle function has been attributed to changes in both the nervous and muscular systems 2 . Prior work has indicated that there is progressive decline in muscle function (e.g., strength) beginning around 30 years of age with an accelerated loss after 60 years of age 3 , 4 . The age-related reduction in muscle strength is notably greater than the loss of muscle mass 5 , which indicates that other changes in the neuromuscular system beyond atrophy are mechanistically associated with the loss of muscle function 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…That is, lower-limb CG compared with upper-limb or combined application of the garment might be more effective to reduce exercise-induced decrements in muscle strength [33,[61][62][63][64][65][66], especially 24 h following physical exercise [5]. Although some researchers suggested that experimentally induced muscle fatigue affects the generation of mechanical work and power in lower-limb joints even during gait [69,70], a previous study found no effects of hundreds of sit-to-stand trials on knee MVIC in healthy younger and older adults [71]. A previous review discussed that muscle fatigue induced by repetitive single-joint muscle contractions such as knee extension-flexion is most probably due to a localized force impairment, while when a multi-joint fatiguing protocol is used (e.g., sit-to-stand task, 6-min walk test), any adaptation in gait after the task is the result of a combined physiological and cognitive effect [72].…”
Section: Introductionmentioning
confidence: 99%